Improving Business Performance For A Food Equipment Supplying Company - Lim, Yu Yin (2014)
Food processing equipment industry is playing an important role to support the growth in the food processing industry in Malaysia. This industry has evolved from the basic equipment assembly works and installation services, moving into the wide scope of services such as project management, engineering designs, fabrication, and transfer of food processing technology. The growth of this industry is moving in tandem with the development of agribusiness and food processing industry in this region. BWE Sdn Bhd had been selected as the case study with an aim to understand an organisation how to develop a small business which establish merely as an engineering service provider into a total solution service provider for designing and fabricating of refrigeration system as well as the distribution of food processing equipment.